Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.jsps.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

An influence of adrenaline (1:80,000) containing local anesthesia (2% Xylocaine) on glycemic level of patients undergoing tooth extraction in Riyadh

Abstract: The study concluded no significant effect on the glycemic level of patients after the administration of local anesthesia containing adrenaline 1:80,000 in healthy and diabetic patients whether hypoglycemic medication was taken or not but a rise in blood sugar level was found among diabetic patients who did not take their hypoglycemic medications undergoing tooth extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Besides that there was no statistically significant difference in blood glucose levels of patients undergoing both treatments suggesting the clinical feasibility of epinephrine or felypressin administration for patients with this profile. The results of this study corroborate with Haji et al 14 and Khawaja et al 17 showing that the use of lidocaine associated to epinephrine does not present significant difference in the blood glucose alterations for compensated diabetic patients. In addition, Santos-Paul et al 18 conducted a study and demonstrated that epinephrine associated to lidocaine did not lead to hyperglycemia significant changes either in hemodynamics or in anxiety parameters in type 2 diabetic and coronary disease patients.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Besides that there was no statistically significant difference in blood glucose levels of patients undergoing both treatments suggesting the clinical feasibility of epinephrine or felypressin administration for patients with this profile. The results of this study corroborate with Haji et al 14 and Khawaja et al 17 showing that the use of lidocaine associated to epinephrine does not present significant difference in the blood glucose alterations for compensated diabetic patients. In addition, Santos-Paul et al 18 conducted a study and demonstrated that epinephrine associated to lidocaine did not lead to hyperglycemia significant changes either in hemodynamics or in anxiety parameters in type 2 diabetic and coronary disease patients.…”
Section: Resultssupporting
confidence: 91%
“…The use of adrenergic vasoconstrictor as epinephrine regarding local anesthesia in diabetic patients has been treated in the literature [17][18] effect of epinephrine in cellular glycogen breakdown is observed, leading to hyperglycemia Moreover, few studies have compared the effects of epinephrine and felypressin in blood glucose in diabetic patients, leading to this research.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Corbati I. et al in the United Kingdom reported that 20% of dentists used anesthesia without vasoconstrictors for uncontrolled diabetic patients. Another study conducted by A. Vander Auwera et al showed that only 25.3% of participants choosed anesthesia without vasoconstrictors among this type of patient [14] [15].…”
Section: Discussionmentioning
confidence: 93%
“…Khawaja et al concluded that the use of epinephrine in local anesthesia is safe in healthy and diabetic patients under hypoglycemic medications. 22 Alves dos Santos-Paul et al observed that the use of epinephrine (1:100,000) does not interfere with BGLs on pharmacologically controlled type 2 diabetes patients. 23 …”
Section: Discussionmentioning
confidence: 99%